2011
DOI: 10.1093/icvts/ivr087
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic enigma: primary pulmonary artery sarcoma

Abstract: Primary angiosarcoma of pulmonary artery is a very rare lesion. We present a case of primary angiosarcoma that was initially misdiagnosed as a subacute massive pulmonary thromboembolism in a 30-year-old man. This rare disease is usually indistinguishable from acute or chronic thromboembolic disease of the pulmonary arteries. The clinical and radiological findings of pulmonary artery angiosarcoma are similar to those of pulmonary thromboembolism. Although the incidence of pulmonary artery angiosarcoma is very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 6 publications
(1 reference statement)
0
19
0
1
Order By: Relevance
“…When diagnosing PAS, the first step is to rule out the possibility of a metastatic tumor from other regions of the body (11). PAS is a rare malignant tumor with an incidence of 0.001-0.030%, and the pathogenesis of the disease remains unclear (2). PAS has been previously reported in patients aged 13-86 years, with a mean age of 52 years old, and a female-to-male ratio of 2:1 (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When diagnosing PAS, the first step is to rule out the possibility of a metastatic tumor from other regions of the body (11). PAS is a rare malignant tumor with an incidence of 0.001-0.030%, and the pathogenesis of the disease remains unclear (2). PAS has been previously reported in patients aged 13-86 years, with a mean age of 52 years old, and a female-to-male ratio of 2:1 (9).…”
Section: Discussionmentioning
confidence: 99%
“…It has an incidence rate of 0.001-0.030% (2). Since 1923, when the first case of PAS was reported by Mandelstamm (3), ≤300 cases have been reported to date worldwide (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the heart rhythm was regular and pulmonary valve section two (P2) heart sound hyperthyroidism and bilateral lower extremity edema were observed. The results of the laboratory tests (Automatic Blood Cell Analyzer; Sysmex XE2100; Sysmex Medical Electronics Co., Ltd., Kobe, Japan) were as follows: White blood cells (WBC), 7.1x10 9 /l (normal range, 3.5-9.5x10 9 /l); red blood cells (RBC), 5.70x10 12 /l (normal range, 3.8-5.1x10 12 /l); hemoglobin (Hb), 146 g/l (normal range, 115-150 g/l); platelets (BPC), 134x10 9 /l (normal range, 125-350x10 9 /l); and D-dimer, 270 mg/l (normal range, 0-230 mg/l; Dimertest Latex kit; Shanghai Boatman Biotech Co., Ltd., Shanghai, China). Normal results were obtained in the routine examination of stools and urine.…”
Section: Case Reportmentioning
confidence: 99%
“…Clinically, PAS can easily be misdiagnosed as a pulmonary thromboembolic disease, such as pulmonary thromboembolism (PTE) or chronic thromboembolic pulmonary hypertension (CTEPH) (5-7). In such instances, patients lose the opportunity for early diagnosis and treatment (8,9). In the present study, the clinical data of three patients with PAS, as confirmed by surgery at the Beijing Anzhen Hospital (Beijing, China), are reported and analyzed, in order to raise awareness and improve the diagnosis of PAS.…”
Section: Introductionmentioning
confidence: 98%